EEBEE (Edible Film Euchema Cottoni Beeswax): Edible Film Based on Carrageenan Seaweed and Beeswax - Aisha Safira Hadi; Aulia Maqdum Ahsani; Maisa Shofwatunnisa; Nisrina Salsabila Hikmawan; Ratu Arta Kinasih (SMA Trensains Muhammadiyah Sragen, 2022)
Edible film is a thin layer as packaging of food products that can be eaten together with packaged products (food grade). Edible film is a development of biodegradable plastics. Edible film made from carrageenan generally has disadvantages as food packaging, namely less resistant to pathogenic bacteria and its low ability as a barrier to water vapor transfer. Therefore, this research was carried out as a form of development of innovations from Edible film that is able to prevent the entry of pathogenic bacteria by adding garlic extract containing allicin compounds and increasing physical properties in resisting the rate of water vapor transmission. This study aims to determine the effect of the addition of beeswax and garlic extract on the edible film characteristics of E.cottoni seaweed carrageenan and as an effort to reduce plastic-based food packaging that is difficult to decompose. The research method used is qualitative description. The parameters tested were thickness, tensile strength, elongation, odor, turbidity, and color. The results showed that the characteristics of edible films made from 2% caragenan with the addition of 0.3% beeeswax and 0.5% garlic extract had a tensile strength of 14.53 ± 15.70, elongation 15.89 ± 25.98%, thickness 0, 05 ± 0.07 mm, normal odor garlic with a lower level, producing a pale yellowish white color and slightly turbid.